Routes of Exposure (Inhalation, Ingestion, Dermal Contact) of Heavy Metals and Their Implications for Human Health - Shukla P.; Srivastava P.; Mishra A. (My University, 2025)
Researchers have for centuries paid much consideration to environmental issues. Even in the era of technological advancement in drinking water, the quantity of heavy metals continues to exceed the standards set by regulatory organizations in many countries worldwide. Toxic metals have been showcased to give rise to a consequential risk to the health of humans because of their capacity to adversely affect DNA and lipids and obstruct the function of proteins and enzymes. By catalyzing the oxidation of amino acid side chains, binding to functional groups, changing the way proteins fold, and/or substituting for essential metal ions in enzymes, these metallic elements disrupt the structural integrity of native proteins. Heavy metal bioaccumulation, mechanisms of action, and transmission channels are highlighted in this chapter. These pollutants' bioavailability in soil and plant absorption have also been considered. Meanwhile, how heavy metals interact positively and negatively, as well as the toxicity of these interactions alone, is discussed. The chapter demonstrates the interactions of specific hazardous metals with proteins and enzymes and their physiological and biochemical effects. Some detoxification techniques are also highlighted because heavy metal poisoning of the environment is one of the world's biggest concerns today. © 2025 selection and editorial matter Veer Singh, Ashish Kumar, Vishal Mishra and Sachchida Nand Rai; individual chapters, the contributors.